Research and development of the sOLVe Tube™ dual lumen endobronchial tube: from concept to construct - Nwajuaku, Patricia; Barjaktarevic, Igor; Hoftman, Nir (Frontiers in Medical Technology, 2023)
Introduction Dual lumen endobronchial tubes (DLTs) are frequently used for lung isolation and one lung ventilation in thoracic surgery and other specialized clinical scenarios. Modern DLTs are large and rigid, and account for half of all tracheobronchial injuries. Their 70 year old design has numerous flaws which limit their safety and clinical utility. Our research team set out to design a new and improved DLT to mitigate these shortcomings, and then test the proposed device to ensure proper function. Methods Using published airway anatomy data and computed tomography imaging from 195 thoracic surgery patients, we designed a new DLT with a single size/configuration that would fit into adult surgery patients. This single “Universal design” was intended to replace both left and right sided 35Fr-41Fr DLTs (8 total products), while remaining small in diameter (35Fr). Other design goals included: 1) making intubation easier and safer, 2) allowing full sized therapeutic bronchoscopes to fit into this tube, 3) making the DLT more resistant to dislodgement. After design process completion the proposed dimensions were tested against 195 patients' left and right mainstem bronchi for radiographic fit. Once production prototypes were manufactured, they were tested in large adult Yorkshire pigs and fresh human cadavers for anatomic fit and performance. Results The proposed design passed the radiographic fit test in all 195 patients for both left and right mainstem endobronchial placement. Intubation was successful and deemed atraumatic in all pigs and cadavers, and the device appropriately fit in both the right and left mainstem bronchi. Lung isolation was successfully achieved and the device proved resistant to axial force dislodgement. Conclusion We propose a new design for a novel DLT meant to replace 8 currently supplied adult configurations with a single, one size/configuration fits all product that allows for large bore bronchoscopy and resists axial force dislodgement.